THE EFFECT OF SUCROSE CONCENTRATION ON THE QUALITY AND ORGANOLEPTIC OF DRIED CANDY TOMATOES - Jufrinaldi Jufrinaldi Jufrinaldi; Suwoto Suwoto; Dicky Tri Jatmiko; Agus Salim Afrozi; Anton Fathoni; Tasya Nia Triani Bate'e (Universitas Trilogi, 2026)
Tomatoes are a high-value horticultural product but are easily damaged and tend to have a short shelf life. Processing tomatoes into candied tomatoes is one way to extend the shelf life of tomatoes. However, tomato processing such as the addition of sucrose can affect the quality and consumer acceptance. This study was designed using a complete randomized design with 1 variable, namely sucrose concentration of 20, 30 and 40%. The stages of this study consisted of sampel preparation, making candied tomatoes and characterizing candied tomatoes including water content, vitamin C, sucrose, and color and organoleptic tests. The results of the analysis showed that there were significant differences between each treatment with sucrose concentrations of 20, 30 and 40% with moisture content variations of sucrose addition to the moisture content of 25.53, 18.78 and 15.40%, total sucrose content worth 28.95, 41.10 and 50.56%, vitamin C content of 5.60, 4.59 and 3.65%, respectively. Color characteristics also showed significant differences, including Lightness of 39.25, 31.30, and 29.02, a* of 4.14, 13.29, and 8.75, b* of 5.83, 7.57, and 6.54, Chroma of 7.47, 15.35, 11.27, hue of 58.14, 29.70, and 43.83, Whiteness Index of 38.80, 29.62, 28.18 and Browning Index of 23.18, 56.45, and 45.23 respectively. And the organoleptic test results showed that the 20% sucrose content treatment tended to be the most preferred with a favorability score of 3.45.